Reproduction and Fertility Beliefs, Perceptions, and Attitudes in People Living with HIV - Vaidehi Mujumdar; Doris Berman; Katherine R. Schafer (AIDS Research and Treatment)
People living with HIV (PLWH) have distinct needs when it comes to reproductive health, specifically regarding fertility, family planning, and pregnancy, and these needs are often complicated by HIV status. While there is ample research that focuses on reproductive health in PLWH through a quantitative lens, there is a lack of research using qualitative methods, namely, the narrative interview model. We searched PubMed and relevant abstracts to identify 72 articles published from 1997 to 2016 that described a qualitative framework for exploring the behaviors and perceptions regarding family planning, abortion, pregnancy, parenthood, fertility, and forced sterility in PLWH. The inclusion criteria initially showed 147 articles, which were further screened to exclude those that did not address fertility and family planning specifically. Our final sample of articles included articles related to qualitative research on reproductive attitudes, beliefs, and behaviors of PLWH. Several of these articles were mixed-methods analyses, but our focus was on the qualitative portion only. Further qualitative works in this area will not only contribute to gaps quantitative research in the field cannot capture by design, but also inform clinical practice, policy, and interventions through systematic, in-depth evaluation.